Soil Amendment With Organic Products Increases the Production of Prickly Pear Cactus as a Green Vegetable (Nopalitos) - Murillo-Amador, Bernardo; Flores-Hernández, Arnoldo; García-Hernández, José Luis; Valdez-Cepeda, Ricardo David; Ávila-Serrano, Narciso Ysac; Troyo-Diéguez, Enrique Troyo-Diéguez; Ruiz-Espinoza, Francisco H. (Journal of the Professional Association for Cactus Development, 2005)
In this work, the effect of organic fertilization in the production of young cladodes (nopalitos) (cladode sprouts) in prickly pear was studied. The treatments of organic fertilizers used were: T1 = 75% soil + 23% compost + 2% red crab flour; T2 = 75% soil + 23% compost + 2% fish flour; T3 = 75% soil + 25% compost; T4 = 75% soil + 25% cow manure; and T5 = soil only (control), which were arranged in a complete randomized block design with five replications. The data were analyzed using univariate and multivariate analysis of variance and multiple comparison means (Tukey p=0.05) when the variables showed significant statistical differences among treatments. The results indicate that all variables showed significant differences among treatments, including the multivariate analysis. All variables showed the highest values in treatment T2 and this treatment was the better combination of organic matter and animal source (terrestrial and marine), i.e., compost + fish flour. In general, the treatments with organic fertilization increased the production of nopalitos in comparison with the control treatment.